The Role of Environmental Attitude as Mediator Between Perceived Sustainability Policy and Spiritual Well-Being Toward Pro-Environmental Behavior: [Peran Environmental Attitude Sebagai Mediator Perceived Sustainability Policy dan Spiritual Well-Being Atas Pro-Environmental Behavior] - Soeharso, Silverius Y.; Ningtyas, Lisa Dwi; Sundari, Resy (Faculty of Psychology, Universitas Surabaya, 2023)
This study aims to ascertain the role of the environmental attitude (EA) variable as a moderator in the relationship between perceived sustainability policy (PSP) and spiritual well-being (SpWB) on pro-environmental behavior (PEB). The sampling technique utilized was convenience sampling, and 127 respondents were selected, consisting of lecturers and education staffs at several universities in DKI Jakarta. The measuring instruments utilized are the Pro-Environmental Behavior (PEB) Scale, Environmental Attitude (EA) Scale, Perceived Sustainability Policy (PSP) Scale, and Spiritual Well-Being (SpWB) Scale; with Structural Equation Model (SEM) as the data analysis. The conclusion is that the relationship model consisting of the variables pro-environmental behavior (PEB), environmental attitude (EA), spiritual well-being (SpWB), and perceived sustainability policy (PSP)